Energy and economic growth. An empirical analysis - Antonios ADAMOPOULOS (Theoretical and Applied Economics, 2021)

(untitled)
This study investigates the interrelation between energy and economic growth for USA covering the time period from 1975 to 2017. Ordinary least squares method and the essential diagnostic tests are applied in order to examine the possible existence of autocorrelation, specification, heteroscedasticity and normality tests for residuals of estimated equation model. The empirical results of this study indicated that there is a linear and positive relationship between energy and economic growth for USA.